2004
DOI: 10.1111/j.1600-0684.2004.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell‐mediated protective efficacy of a systemic vaccine approach in cynomolgus monkeys after SIV mucosal challenge

Abstract: The immunogenicity and the protective efficacy of a new polyvalent triple vector (DNA/SFV/MVA) based vaccine against mucosal challenge with pathogenic SIVmac251 were investigated. Cynomolgus monkeys (Macaca fascicularis) were primed intradermally with DNA, boosted twice subcutaneously with recombinant Semliki Forest virus (rSFV) and finally intramuscularly with recombinant Modified Vaccinia Virus Ankara strain (rMVA). Both DNA and recombinant viral vectors expressed SIV proteins (Gag, Pol, Tat, Rev, Nef and En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Previous work has shown that Cynomolgus macaques generally (65,66), and Mauritian origin Cynomolgus macaques in particular (67)(68)(69), can be infected with pathogenic SIV and develop sAIDS. When compared with Indian Rhesus macaques, Cynomolgus macaques require a higher dose of virus to consistently establish SIV infection (68) and maintain lower viral loads more similar to HIV-infected humans (66).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that Cynomolgus macaques generally (65,66), and Mauritian origin Cynomolgus macaques in particular (67)(68)(69), can be infected with pathogenic SIV and develop sAIDS. When compared with Indian Rhesus macaques, Cynomolgus macaques require a higher dose of virus to consistently establish SIV infection (68) and maintain lower viral loads more similar to HIV-infected humans (66).…”
Section: Discussionmentioning
confidence: 99%
“…Cynomolgus macaques are used for preclinical vaccine evaluation. Various vector strategies have been tested, including DNA, recombinant Semliki Forest and modified recombinant vaccinia virus strain Ankara (MVA) (33,39,40). It is not known whether cynomolgus macaques are easier or not to protect in a vaccination protocol against simian AIDS than Indian rhesus monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…This system allows the packaging of suicidal, singleround infectious viral particles (23) that have been shown to stimulate protective immunity in a number of different infection models (2,13,34,35). The potential of rSFV as a valuable component of a vaccine against HIV-1 has also been demonstrated, but these studies have primarily focused on the ability of rSFV to stimulate CD8 ϩ T-cell responses (21,33,37). Here, we have characterized the ability of recombinant Semliki Forest virus (rSFV) particles to express soluble YU2gp140 (-/GCN4) trimers in vitro and compared their expression to monomeric YU2gp120 proteins expressed by rSFV.…”
mentioning
confidence: 99%